Invisible Support: Effects on the Provider's Positive and Negative Affect. Issue 2 (28th April 2016) - König, Claudia; Stadler, Gertraud; Knoll, Nina; Ochsner, Sibylle; Hornung, Rainer; Scholz, Urte
Abstract : Background: Social support that goes unnoticed by receivers (i.e. invisible support) seems to be most beneficial for the receivers' well‐being. The providers' well‐being, however, has been neglected so far. This study examines how invisible support is related to the providers' well‐being and whether this association is dependent on the providers' relationship satisfaction. Methods: Overall, 97 non‐smoking partners of smokers who were about to quit smoking were examined. Invisible support was assessed dyadically: partners' reports on smoking‐specific provided social support together with smokers' reports on received support were assessed at baseline. Partners' relationship satisfaction was also assessed at baseline. Partners' positive and negative affect were measured at baseline and six‐week follow‐up. Results: No main effects of invisible instrumental or emotional support occurred. However, partners' relationship satisfaction moderated the association between invisible instrumental support and change in partners' negative and positive affect: For partners with lower relationship satisfaction more invisible instrumental support was related to increased negative affect and decreased positive affect, whereas for partners with higher relationship satisfaction the inverse effects occurred. Conclusions: The study's results emphasise that invisible instrumental support might have emotional costs for the providers. Relationship satisfaction seems to serve as a protective factor.